A systematic review of pharmacological treatment options used to reduce ischemia reperfusion injury in rat liver transplantation - Yamanaka, Kenya; Houben, Philipp; Bruns, Helge; Schultze, Daniel; Schemmer, Peter (PLOS ONE, 2015)
Background Although animal studies models are frequently used for the purpose of attenuating ischemia reperfusion injury (IRI) in liver transplantation (LT), many of pharmacological agents have not become part of clinical routine. Methods A search was performed using the PubMed database to identify agents, from which 58 articles containing 2700 rat LT procedures were selected. The identified pharmacological agents were categorized as follows: I - adenosine agonists, nitric oxide agonists, endothelin antagonists, and prostaglandins, II - Kupffer cell inactivator, III - complement inhibiter, IV - antioxidant, V - neutrophil inactivator, VI -anti-apoptosis agent, VII - heat shock protein and nuclear factor kappa B inducer, VIII - metabolic agent, IX - traditional Chinese medicine, and X - others. Meta-analysis using 7-day-survival rate was also performed with Mantel-Haenszel's Random effects model. Results The categorization revealed that the rate of donor-treated experiments in each group was highest for agents from Group II (70%) and VII (71%), whereas it was higher for agents from Group V (83%) in the recipient-treated experiments. Furthermore, 90% of the experiments with agents in Group II provided 7-day-survival benefits. The Risk Ratio (RR) of the meta-analysis was 2.43 [95% CI: 1.88-3.14] with moderate heterogeneity. However, the RR of each of the studies was too model-dependent to be used in the search for the most promising pharmacological agent. Conclusion With regard to hepatic IRI pathology, the categorization of agents of interest would be a first step in designing suitable multifactorial and pleiotropic approaches to develop pharmacological strategies.